Energy nature's power source (Viewtech Education, 2000)
"Energy is the capacity to produce power. Where does it come from, and how is it used? This illuminating two-part series provides a solid grounding in the basics of potential and kinetic energy while promoting a healthy awareness of the pros and cons associated with energy generation. The applications of energy to industrial, commercial, residential, and transportation needs are presented, as well as the advantages and disadvantages of the various sources of renewable and exhaustible energy, the impact of energy generation on the environment, estimates of the world's remaining supplies of energy-producing materials, and the importance of conservation"